Freshmen's Perception on Inductive Approach through PPP (Presentation, Practice, Production) Phase in Their First Speaking Class - Irawati, Erna (Journal of English Education Studies, 2018)
This research investigates freshmen’s perception on inductive approach through PPP phase in their first speaking class. The researcher tries to integrate the previous students learning experience that were accustomed to the deductive approach with the inductive approach as the solution by implementing the PPP phase. The research is based on qualitative approach with descriptive method. 38 first semester students from English Education Study Program of teacher Training and Education Faculty, Universitas Mathla’ul Anwar Banten were assigned as participants. Questionnaire was evaluated to get insight about freshmen’s perception on Inductive Approach through PPP phase in their first speaking class. As a result, the study reveals that the student's response to all aspects of learning get a high response, 83.11% for inductive approach, 95.39% for PPP phase, and 100% for speaking activity. As the final remark, this means that students give a positive response on inductive approach through PPP phase in their first speaking class with the average score of all aspects 92.84%.